DNA-binding proteins and evolution of transcription regulation in the archaea. - Aravind, L (1999)
Likely DNA-binding domains in archaeal proteins were analyzed using sequence profile methods and available structural information. It is shown that all archaea encode a large number of proteins containing the helix-turn-helix (HTH) DNA-binding domains whose sequences are much more similar to bacterial HTH domains than to eukaryotic ones, such as the PAIRED, POU and homeodomains. The predominant class of HTH domains in archaea is the winged-HTH domain. The number and diversity of HTH domains in archaea is comparable to that seen in bacteria. The HTH domain in archaea combines with a variety of other domains that include replication system components, such as MCM proteins, translation system components, such as the alpha-subunit of phenyl-alanyl-tRNA synthetase, and several metabolic enzymes. The majority of the archaeal HTH-containing proteins are predicted to be gene/operon-specific transcriptional regulators. This apparent bacterial-type mode of transcription regulation is in sharp contrast to the eukaryote-like layout of the core transcription machinery in the archaea. In addition to the predicted bacterial-type transcriptional regulators, the HTH domain is conserved in archaeal and eukaryotic core transcription factors, such as TFIIB, TFIIE-alpha and MBF1. MBF1 is the only highly conserved, classical HTH domain that is vertically inherited in all archaea and eukaryotes. In contrast, while eukaryotic TFIIB and TFIIE-alpha possess forms of the HTH domain that are divergent in sequence, their archaeal counterparts contain typical HTH domains. It is shown that, besides the HTH domain, archaea encode unexpectedly large numbers of two other predicted DNA-binding domains, namely the Arc/MetJ domain and the Zn-ribbon. The core transcription regulators in archaea and eukaryotes (TFIIB/TFB, TFIIE-alpha and MBF1) and in bacteria (the sigma factors) share no similarity beyond the presence of distinct HTH domains. Thus HTH domains might have been independently recruited for a role in transcription regulation in the bacterial and archaeal/eukaryotic lineages. During subsequent evolution, the similarity between archaeal and bacterial gene/operon transcriptional regulators might have been established and maintained through multiple horizontal gene transfer events.